1993
DOI: 10.1038/366178a0
|View full text |Cite
|
Sign up to set email alerts
|

Tandem binding in crystals of a trp represser/operator half-site complex

Abstract: The crystal structure of trp repressor tandemly bound in a 2:1 complex to a 16-base-pair palindromic DNA containing a central trp operator half-site has been determined and refined to 2.4 A resolution. Despite dramatically different DNA sequence contexts and crystallization conditions, the protein/DNA interface is essentially identical to that seen in the original trp repressor/operator complex structure. Water-mediated sequence recognition by trp repressor is likely to be related to the unusual end-on approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
121
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(129 citation statements)
references
References 25 publications
6
121
1
Order By: Relevance
“…1D). We chose residue 11 as the amino-terminal boundary of TrpR because this amino acid is the first helical residue in the crystal structure (35). Upon purification, we found that FMN binding and reversible photobleaching are preserved in all constructs (27).…”
Section: Discussionmentioning
confidence: 99%
“…1D). We chose residue 11 as the amino-terminal boundary of TrpR because this amino acid is the first helical residue in the crystal structure (35). Upon purification, we found that FMN binding and reversible photobleaching are preserved in all constructs (27).…”
Section: Discussionmentioning
confidence: 99%
“…Its structure in both the Trp-free apo-form and the Trp-bound holo-form, and the structure of its DNA complexes, have been determined by both X-ray and NMR analyses (Schevitz et al, 1985;Otwinowski et al, 1988;Lawson & Carey, 1993;Zhao et al, 1993;Zhang et al, 1994). The repressor is known to interact with at least five different operator sequences, i.e., in the trp, trpR, aroH, aroL, and mtr operons Reprint requests to: Oleg Jardetzky, Stanford Magnetic Resonance Laboratory, Stanford University, Stanford, California 94305.5055; e-mail: jardetzky@camis.stanford.edu.…”
Section: " " ~~~mentioning
confidence: 99%
“…Structures are known for the corepressor-free and -bound forms of only two other repressors: the tryptophan repressor (TrpR) (27,(31)(32)(33) and the methionine repressor (MetJ) (34 -36). The TrpR and MetJ repressors are similar in that they both bind their corepressors within their DNA-binding domains.…”
Section: Fig 2 Structure Of the Purr-guanine-purf Operator Complexmentioning
confidence: 99%